Pengaruh rasio keuangan, karakteristik perusahaan dan tarif pajak terhadap struktur modal perusahaan otomotif yang terdaftar di bursa efek Indonesia - ERIKA JIMENA ARILYN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2015)
The purpose of this research is to test and analyze empirically the influence of profitability, firm size, asset structure, growth, ownership structure, and tax rate toward capital structure. The sample in this research is automotive industry which is listed in Indonesia Stock Exchange over 12 years period 2002 until 2013. This research used purposive sampling method. Only 6 companies met the criteria and were analyzed using descriptive statistics and multiple regressions for panel data with fixed effect model were performed to test the hypotheses. The result of this research showed that firm size have influence toward capital structure, while profiability, asset structure, growth, ownership structure, and tax rate do not have influence toward capital structure.